A Survey on the Tax Policy in EU - Adrian Mihai INCEU; Dan Tudor LAZĂR; Eugenia Ramona NANDRA; Radu NECHITA (Transylvanian Review of Administrative Sciences, 2007)
In this study we make an analysis of the major aspects concerning the tax policy in the EU countries. For revealing a global image on tax policy within the EU we have to consider in our analysis the overall tax burden, the structure of tax revenues (direct taxation, indirect taxation, social contributions) and the main types of taxes: corporate tax, personal tax, consumption tax. This article is based on a dynamic analysis of taxation using as a main tools descriptive and empirical analysis. The empirical study tries to determinate the correlation between tax burden and the implicit tax rate on capital and business income, consumption and labor through the panel methodology. This analysis is based the data delivered by the EUROSTAT. The main results obtained from the empirical study is that there are major differences concerning the correlation between total taxes as percentage of GDP and the implicit tax rate of profit, consumption and labor.